Prediction of Lumbar Disk Herniation and Clinical Outcome Using Quantitative Magnetic Resonance Imaging: A 5-Year Follow-Up Study. Issue 3 (March 2019) - Raudner, Marcus; Schreiner, Markus M.; Juras, Vladimir; Weber, Michael; Stelzeneder, David; Kronnerwetter, Claudia; Windhager, Reinhard; Trattnig, Siegfried
Abstract : Objectives: The aim of this study was to assess the predictive value of T2 mapping at baseline with regard to the development of disk herniation and clinical outcome at a 5-year follow-up in patients with low back pain. Materials and Methods: Twenty-five symptomatic patients (13 male; mean age, 44.0 years; range, 24–64 years at baseline) were examined at 3 T magnetic resonance imaging, with a 5-year follow-up. Region of interest analysis was performed on 125 lumbar intervertebral disks on 2 central sagittal T2 maps. Absolute T2 relaxation times and a T2 value ratio of the posterior annulus fibrosus as a percentage of the nucleus pulposus (NPAF) were evaluated for each disk. All disks were graded morphologically using the Pfirrmann score. Roland-Morris Disability Questionnaires (RMDQ) and a visual analogue scale (VAS) were assessed for each patient at follow-up as a clinical end point and compared with diagnosed lumbar disk herniation. Statistical analysis was conducted by a biomedical statistician. Results: Using the baseline NPAF ratio, follow-up development of herniation was predicted with an area under the curve (AUC) of 0.893 in a receiver operating characteristic curve. The same was done using the baseline nucleus pulposus T2, resulting in an AUC of 0.901. Baseline and follow-up NPAF, as well as baseline and follow-up nucleus pulposus T2, differed significantly ( P < 0.001) between disks with no herniation, disks with herniation at baseline, and disks with new herniation at follow-up. Difference was still significant (all P < 0.001), when only testing for difference in degenerated discs with Pfirrmann score III to V. Calculating sensitivity and specificity for herniation prediction only in discs with Pfirmann III to V using a receiver operating characteristic, AUC was 0.844 with baseline herniations excluded. The lowest baseline nucleus pulposus T2 per patient correlated significantly with follow-up RMDQ ( r = −0.517; P = 0.008) and VAS ( r = −0.494; P = 0.012). The highest baseline NPAF correlated significantly with RMDQ ( r = 0.462; P = 0.020), but not VAS ( r = 0.279; P = 0.177). Conclusions: Quantitative T2 mapping may serve as a clinically feasible, noninvasive imaging biomarker that can indicate disks at risk for herniation and correlates with clinical outcome and subjective patient burden in a representative cohort of patients with low back pain.